The Effect of Mocaf Flour Substitution and Ciplukan Fruit Addition on the Preference Level of Nastar Cookies - Rohman, Fathur; Bahar, Asrul; Sari, Fitri Komala; Nuraini, Annisa (Universitas Negeri Padang, 2025)
Nastar cookies are traditionally made using wheat flour as the main ingredient. Indonesia’s dependence on imported wheat encourages the use of local ingredients such as mocaf flour (modified cassava flour) and product enrichment with ciplukan fruit (Physalis angulata L.), which contains various bioactive compounds. This study aimed to determine the effects of mocaf flour substitution and ciplukan fruit addition on the preference level of nastar cookies. The research employed a completely randomized design (CRD) with a 3×2 factorial arrangement, resulting in six treatment combinations. The treatments consisted of mocaf flour substitution levels of 40%, 60%, and 80%, and ciplukan fruit additions of 30% and 40%. Hedonic testing was conducted with 50 semi-trained panelists using a four-point scale to evaluate color, aroma, texture, taste, and overall acceptance as response variables. Data were analyzed using two-way ANOVA to examine the main and interaction effects, followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level (p < 0.05). The results indicated that mocaf flour substitution significantly affected color (p < 0.05), while ciplukan fruit addition significantly influenced color, aroma, and overall acceptance (p < 0.05). No significant interaction between the two factors was observed. The best treatment was obtained from the combination of 80% mocaf flour substitution and 30% ciplukan fruit addition (M3.C1). These findings indicate that incorporating up to 80% mocaf and 30% ciplukan fruit yields nastar cookies with superior sensory quality and supports the diversification of local food ingredients.